CLONING, EXPRESSION OF EcCSPA GENE AND PURIFICATION OF ITS PROTEIN - Nizkorodova, A.S.; Polyanskaya, E.V.; Smagulov, A.M.; Iskakov, B.K. (Eurasian Journal of Applied Biotechnology, 2013)
Cold-shock proteins (CSPs) are expressed in all living cells as the part of acclimation reaction to temperature decrease. These proteins are able to bind single stranded nucleic acids; it is also shown that some of cold-shock proteins are RNA chaperons. The mechanism of action during the cold-stress for these proteins is not completly understood yet. It’s thought that CSPs can inhibit expression of majority of cellular proteins via unspecific binding to their mRNAs during the cold-shock. On the other hand CSPs can act as RNA chaperons, which are thought to facilitate translation by destabilizing secondary structures occurring in mRNAs with decrease of temperature and interfering with their translation. To define CSP’s cell functions some in vitro experimental procedures are required, that presupposes existence of highly-purified and functionally active CSPs. Existing CSPs purification procedures are complicated, expensive and take long time. In this research we present one-stage CSP purification method, approved on EcCSPA. The procedure is based on affinity chromatography with usage of commercial nickel-nitrilotriacetate (Ni-NTA) agarose, which is able to specifically bind histidine sequences (His-tag). All protein purification procedure, including expression in bacterial cells, lasts one laboratory day. Applying this procedure for EcCSPA purification we have obtained native EcCSPA protein with purity 92,8% and concentration 2,9 g per liter of initial bacterial suspension.